Learning bioethics based on problems (LBBP): a new pedagogical focus - Garzón Díaz, Fabio Alberto; Zárate, Betty (Acta Bioethica, 2015)
This article results from research project HUM-948, about the field of bioethics, culture and education by Bioethics Group, Military University of New Granada, presenting the proposal: “Learning bioethics based on problems (LBBP)”. The text is composed of seven parts: (1) an introduction posing the possibility of training and learning bioethics; (2) development of their main characteristics; (3) psycho pedagogic base of LBBP; (4) essential criteria; (5) analysis of epistemological base; (6) a proposal of how to understand LBBP; and (7) as a proposal, 5 issues which should be taken into account when planning a bioethics curricula based on problems and competencies.